Med14 phosphorylation shapes genomic response to GLP-1 agonists - Sam Van de Velde; Jungting Yu; K. Garrett Evensen; Edmund Pakhlevanyan; April E. Williams; Reuben J. Shaw; Marc Montminy (Proceedings of the National Academy of Sciences, 2026)
Binding of GLP-1 to its receptor in pancreatic beta cells triggers activation of the cAMP pathway and phosphorylation of CREB, leading to induction of cellular target genes containing CREB binding sites. By contrast with their acute effects on beta cell gene expression, chronic exposure of beta cells to stable GLP-1 analogs like Exendin-4 stimulates sustained expression of beta cell-specific genes, leading to increases in beta cell viability and insulin secretion. In a proteomic screen for transcriptional coregulators that contribute to the transcriptional effects of GLP-1, we identified Med14, the scaffolding subunit of the conserved 30 subunit Mediator complex. Exposure to Exendin-4 and other GLP-1 receptor agonists stimulates sustained phosphorylation of Med14 at Ser983, which corresponds to a conserved PKA recognition site. Mutation of Med14 at Ser983 blocked Exendin-4 effects on cellular gene expression by interfering with CREB-mediated activation of beta cell-specific enhancers. Med14 mutation results in higher alpha-to-beta cell ratios and blunted gene regulation in response to Exendin-4 in Ser983-mutant primary mouse islets. Our work reveals how phosphorylation of a general transcription factor in response to GLP-1 analogs triggers a broad genomic response with salutary effects on beta cell function.